Assessment for learning: charting a future in the Malaysian higher education - Nordin, Mohamad Sahari (University of Bandar Lampung, 2013)
Assessment for learning is a significant driver of student learning. It serves as a catalyst for reform in instructional practices, and hence, the centerpiece of educational improvement. This presentation reports an intervention programs designed and implemented by an institution of higher education in Malaysia to capitalize on the potentials of assessment for learning. In addition, it discusses conditions that would enable assessment to facilitate meaningful learning among students of higher learning institutions in particular, and create a vibrant learning ecosystem, in general.